FRI0431 Altered expression of circulating micrornas is related to disease activity and structural damage in ankylosing spondylitis patients. (15th June 2017) - Font, P; Perez-Sanchez, C; Ruiz-Limon, P; Lopez-Pedrera, C; Castro-Villegas, MC; Άbalos-Aguilera, MC; Barbarroja, N; Rosa, I Arias-de la; Lopez-Montilla, MD; Escudero-Contreras, A; Lopez-Medina, C; Collantes-Estevez, E; et al.
Abstract : Background: Ankylosing spondylitis (AS) remains difficult to diagnose before irreversible damage to sacroiliac joint is noticeable. MicroRNAs (miRNAs) are a group of single-stranded non-coding RNAs of 20–25 nucleotides in length that can potentially regulate every aspect of cellular function. Recent studies have demonstrated that miRNAs can be detected in the circulation and serve as potential biomarkers of various inflammatory pathologies. Objectives: To evaluate whether AS pathogenesis is related to the aberrant expression of plasma miRNAs. Methods: The expression profile of 800 miRNAs in plasma was determined in pooled samples from AS patients and healthy donors (HDs) (n=3 each) using the nCounter technology. Next, candidate miRNAs were validated by real time RT-PCR in a cohort of AS patients and HDs (n=26 each). In parallel, the expression of validated miRNAs was examined in a cohort of 24 psoriatic arthritis (PsA) patients. To evaluate their relevance in the AS pathogenesis, an analysis was performed by using the web-based bioinformatics tool Ingenuity Pathways Analysis (IPA). Association and correlation studies of altered miRNAs with clinical and analytical profile of the AS patients were also performed. AS activity was defined as CRP >5 mg/L and/or BASDAI ≥4 and ESR >20 mm/h. Structural damage was evaluated by mSASSS. Results: In discovery phase, nine miRNAs were differentially expressed (fold change ≥2) in the plasma of AS patients vs. HDs. After validation, higher expression levels of miRNA (miR)-146a-5p, miR-125a-5p, miR-151–3p and miR-22–3p, and lower of miR-150–5p and miR-451a were found in AS vs. HDs. Interestingly, higher miR-146a-5p, miR-125a-5p, miR-151–3p and miR-22–3p expression levels in AS than in PsA patients were further observed. The areas under the curve, generated to assess the accuracy of miRNAs as diagnostic biomarkers for AS, ranged from 0.717 to 0.798; the six-miRNAs signature reached 0.947. Bioinformatics analysis revealed that miRNAs targeted inflammatory and bone remodeling genes, underlying their potential role in this pathology. Indeed, correlation studies showed an association between these six miRNAs and potential target proteins associated to AS pathophysiology. In addition, miR-146a-5p, miR-146a-5p, miR-125a-5p and miR-22–3p expression was increased in active vs. non-active patients. Moreover, miR-150–5p and miR-451a expression was related to the presence of syndesmophytes in AS patients, underlying their association with structural damage. Conclusions: 1) Several miRNAs are found differentially expressed in plasma from AS patients vs. HDs and other chronic inflammatory pathologies as PsA, indicating that these miRNAs may be considered potential biomarkers for AS diagnose. 2) The differential expression of certain miRNAs is associated to disease activity and structural damage. Overall, this study identified a six-plasma miRNAs signature that could be attractive candidates as non-invasive biomarkers for the AS diagnosis, and may help to elucidate the disease pathogenesis. Acknowledgements: Funded by JA PI-0314–2012, SER, and ISCIII (RIER RD16/0012/0015). Disclosure of Interest: None declared